Análise comparativa dos parâmetros de eficiência de um sistema de fotovoltaico bifacial em relação a painéis policristalinos e monocristalinos half cell - Ferruzzi, Yuri (2023)
Bifacial modules have the advantage of capturing sunlight both in the front and back, so they are able to produce greater amounts of energy compared to standard (monofacial) modules. However, its performance depends on the spatial distribution of the incident irradiance on the surface of the rear module, which is strongly affected by various site-specific conditions such as albedo, module height relative to the ground and the angle of inclination. Height change measurements were studied for three types of reflective layer, dystrophic purple Latosol, silver background (TP 40 unpainted) and green background (Ral code 6001) effects of 8 bifacial modules facing north with constant inclination of 35 degrees. The measure of the reflective layer, responded adequately to each layer proposed. The measurements of the pyranometers showed indices of 0.151 for the purple Latosol, 0.415 for the Green color and 0.605 for the Silver color. Following the optimization of the inclination angle of the bifacial modules dependent on the site, albedo and elevation of the module, it was identified that the energy yield of the bifacial module under test increases with the albedo, but in addition, the performance also increases with the height of the modules, values in the order of 16.62% efficiency, in the lowest reflective layer, at 19.32% on the AC side of the inverter. In the most reflective layer (silver) the indexes reach 21.31% on the DC side that are in accordance with the manufacturer’s manual. The statistical analysis "ANOVA" and Tukey test, showed the reliability of the data. Through the simultaneous energy production in conventional polycrystalline and monocrystalline modules, and half Cell monocrystalline, it was possible to compare the energy production relationship between the technologies, which showed a gain of the bifacial system, with higher energy production in all cases, with gains of 13.93% to 31.41% in energy production. Thus, the benefits of using bifacial technology in solar energy systems in relation to the bifacial modules installed. It was also observed that the effect of shading at the bottom of the bifacial modules, the effect of thermal losses, reducing the efficiency of the panels by up to 0.63%. It also observed the effect of frontal shading, showing the versatility of the bifacial modules in producing energy with the partial and total shading of the modules.